Analysis of the main forms and types of commercialization of R&D in developed countries - Sitenko, D.A.; Holienka, M. (Karagandy University of the name of acad. E.A. Buketov, 2022)
Object: Identification the main forms and types of commercialization of developments in developed countries in order to use them in the process of university technology transfer to the regional innovation system Methods: In the course of the study, methods of system analysis, comparative analysis, grouping method, content analysis, methodology of the Global Innovation Index rating were used. Findings: The article considers the main ways of commercialization in the developed countries of the world. It is shown that in many respects successful models of technology transfer have arisen as a result of the adoption at the state level of legislation that stimulates the process of commercialization. The systematization of approaches to the commercialization of the results of innovative scientific research in world practice has been carried out; practical recommendations have been given for managing this process. The article discusses the main schemes for the distribution of royalties from the implementation of intellectual property between an inventor and a scientific organization. The main forms of technology transfer used in developed countries are studied. Conclusions are drawn about the importance of the commercialization of innovations at various levels of the economy, the impact of state policy on the formation of a model for the commercialization of R&D (research and development) results, and the interaction of universities with the business sector. Conclusions: The article identifies the main problems hindering the development of commercialization in Kazakhstan. The importance of technology transfer from universities to industry as a necessary condition for the development of an innovative economy is substantiated. The main characteristics of universities that conduct active scientific research are revealed. The main forms of technology transfer used in developed countries are identified, which include patenting, licensing agreements, fulfillment of orders for R&D, creation of spin-off companies. The experience of organizational and legal support of commercialization in developed countries is systematized, which is of interest for the development of technology transfer in developing countries.
Дамыған елдердегі әзiрлемелердi коммерцияландырудың нeгiзгi формалары мен түрлерiн талдау
Анализ основных форм и типов коммерциализации разработок в развитых странах
Keywords: commercialization; university; technology transfer; third mission; innovation